The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jtcme.2019.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Gel formulations of Merremia mammosa (Lour.) accelerated wound healing of the wound in diabetic rats

Abstract: Background and aim The treatment of diabetic ulcers is difficult because of defective blood vessels and frequent co-occurrence of bacterial infections. In a previous study, we found a water fraction of Merremia mammosa (Lour.) (Mm(Lour.)) had beneficial effects on wound healing in diabetic rats. This study aimed to evaluate the influence of different gelling agents added to Mm(Lour.) water fraction gel on wound healing treatment in diabetic rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…1 Hyperglycemia can interfere with the regulation of cellular functions, such as defective T-cell immunity, abnormalities in leukocyte chemotaxis, phagocytosis, bactericides, and fibroblast and epidermal cell dysfunction. 2 The present study results showed that Lagerstroemia speciosa and aloe vera extracts gel's application affected the wound healing process in the palate of hyperglycemic rats compared to the untreated group. This result was proofed from the significant differences in the FGF-2 expression level in the Lagerstroemia speciosa and aloe vera extracts gel group on the fourteenth observation day (p-value<0.05).…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…1 Hyperglycemia can interfere with the regulation of cellular functions, such as defective T-cell immunity, abnormalities in leukocyte chemotaxis, phagocytosis, bactericides, and fibroblast and epidermal cell dysfunction. 2 The present study results showed that Lagerstroemia speciosa and aloe vera extracts gel's application affected the wound healing process in the palate of hyperglycemic rats compared to the untreated group. This result was proofed from the significant differences in the FGF-2 expression level in the Lagerstroemia speciosa and aloe vera extracts gel group on the fourteenth observation day (p-value<0.05).…”
Section: Discussionmentioning
confidence: 46%
“…The uncontrolled hyperglycemic condition in diabetes can reduce inflammatory processes, angiogenesis, and collagen synthesis in wound healing. 2 Hyperglycemic condition can reduce the function of red blood cells that carry nutrients to the tissues, as well as reduce the efficiency of leukocytes in fighting infection. Narrowing of blood vessels can cause decreased blood flow and oxygen to the wound, so that without adequate nutrition and oxygen, wound healing will occur slowly.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, the leaf and whole plant of M. mammosa, prepared by infusion and maceration, respectively, have been reported to be beneficial in the treatment and management of diabetes [56] and diabetic ulcers [57]. The leaves of M. peltata prepared by maceration have been employed in the treatment of different forms of cancer, diarrhea, abdominal pain, cough, sore eyes, wounds, and inflammation [58].…”
Section: Ethnomedicinal Uses Of Merremia Speciesmentioning
confidence: 99%
“…In another study, Marchianti et al [57] investigated the wound-healing potency of 1.5% M. mammosa plant gel formulations (incorporation of hydroxypropylmethylcellulose (HPMC), Carbopol, or sodium carboxymethylcellulose (Na CMC) into 10% water fraction of the plant's ethanol extract) in diabetic Wistar rats by percentage wound size reduction, vascular endothelial growth factor expression, hydroxyproline levels, and histopathology assessments. Diabetes was induced by streptozotocin (40 mg kg −1 BW, IP), while the wound was excised using the Morton method.…”
Section: Wound Healing Propertymentioning
confidence: 99%
“…Pemberian obat Merremia mammosa (Lour.) secara topikal pada pengobatan penyembuhan ulkus diabetikum, ditunjukkan dengan peningkatan sintesis kolagen dan angiogenesis (Marchianti et al, 2020).…”
Section: J Daun Bidara Upas (Merremia Mammosa Lour)unclassified